Optimization of the Patrol Unit of the Samapta Unit to Prevent the Occurrence of Ordinary Theft in the Legal Area of the Boyolali Police Station - Mahirawan, Irghie (Advances in Police Science Research Journal, 2024)
This final project is motivated by the increase in ordinary theft crimes in Boyolali Regency from year to year. Therefore, this study aims to describe the extent to which the implementation of patrols at the Boyolali Police in preventing ordinary theft and to find out the efforts used by the author in answering this problem are POAC management theory and its management elements (man, money, method, materials). Then for the concept used the concept of optimization, the concept of Samapta, the concept of patrol and theft concept. Furthermore, this research was carried out with a qualitative approach and used field research. The results of this study are that in carrying out patrols and optimizing in preventing theft, it is usually carried out using Perkabaharkam No. 1 of 2017 concerning patrols. The results of the research conducted by the author are that the completeness of the administration before the implementation of the patrol is still not good, such as an order issued after the implementation of the patrol, a lack of personnel from the Personnel Composition List (DSP), while the budget and infrastructure facilities have been fulfilled but need to be used optimally. As well as the need to hold specialization development education and training for patrol members. For the conclusion that can be drawn that the implementation of patrols has not been implemented optimally in preventing ordinary theft, there are still several inhibiting factors that become obstacles in the implementation of patrols. Therefore, the authors suggest that personnel should be proposed according to the Personnel Composition List (DSP) and maximize the use of existing facilities and infrastructure and maximize the performance of personnel to participate in specialization development education (dikbangspes) and training. In addition to increasing cooperation between personnel and the community. The role of the community is no less important in preventing the crime of ordinary theft.